2006
DOI: 10.1038/sj.ijir.3901519
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the relationship between biomarkers of atherosclerosis and erectile dysfunction in 988 men

Abstract: Erectile dysfunction (ED) is associated with clinical atherosclerosis and several atherosclerotic risk factors including smoking, hypertension, dyslipidemia, diabetes mellitus, obesity and sedentary lifestyle. Clinical atherosclerosis is also associated with these same risk factors and with biomarkers of inflammation, thrombosis, endothelial cell activation.We evaluated the crosssectional association between the degree of ED and levels of atherosclerotic biomarkers. A subcohort of 988 US male health profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 34 publications
0
40
2
1
Order By: Relevance
“…10,[19][20][21][22] Several reports have shown that the presence and severity of ED are associated with inflammatory markers and endothelial dysfunction. 23,24 Similar pathogenic involvement of the nitric oxide (NO) pathway leading to the impairment of endothelium-dependent vasodilatation in the early phase, and obstructive vascular changes in the late phase, is shared by ED and other vascular diseases. 25,26 Therefore, atherosclerosis characterized by vascular damage and NO-pathway impairment may partially explain the association between ED, MS and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…10,[19][20][21][22] Several reports have shown that the presence and severity of ED are associated with inflammatory markers and endothelial dysfunction. 23,24 Similar pathogenic involvement of the nitric oxide (NO) pathway leading to the impairment of endothelium-dependent vasodilatation in the early phase, and obstructive vascular changes in the late phase, is shared by ED and other vascular diseases. 25,26 Therefore, atherosclerosis characterized by vascular damage and NO-pathway impairment may partially explain the association between ED, MS and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…20 Indeed, atherosclerotic biomarkers for endothelial function, thrombosis and dyslipidemia are associated with the degree of ED. 21 In a longitudinal population-based study, after adjustment for the classical risk factors, severely decreased erectile rigidity has a hazard ratio of 2.6 and decreased erectile rigidity a hazard ratio of 1.6 for cardiovascular disease. 22 Three-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) decrease the action of oxidized LDL on endothelial cells, resulting in increased NO activity.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods of endothelial function measurement are being used in research studies to establish and further elucidate the link between endothelial dysfunction and ED 4,6,8,9,[85][86][87][88] with the goal of establishing a simple diagnostic test for vasculogenic ED. [80][81][82][83][84][89][90][91] Clinical implications of endothelial function testing…”
Section: Measuring Endothelial Function In Relation To Edmentioning
confidence: 99%